2008
DOI: 10.4161/cc.7.20.6812
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 gamma is required to enforce both the incomplete S phase and G2 DNA damage checkpoints

Abstract: . A 14-3-3γ knockdown clone also showed an override of both checkpoint pathways. These phenotypes were reversed upon expression of a shRNA resistant 14-3-3γ cDNA. Override of the G 2 DNA damage checkpoint pathway was accompanied by a decrease in the levels of inhibitory phosphorylation on cdc25C and cdk1. However, there was no difference in the γ-H2AX foci formation and levels of phospho-chk1 and phospho-chk2, suggesting that activation of the DNA damage checkpoint response and subsequent activation of the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Two isoforms of 14-3-3 family members, ɛ and γ, specifically form heterodimers and interact with cdc25 to regulate the cell cycle [22,23]. Furthermore, 14-3-3 proteins are associated with many types of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Two isoforms of 14-3-3 family members, ɛ and γ, specifically form heterodimers and interact with cdc25 to regulate the cell cycle [22,23]. Furthermore, 14-3-3 proteins are associated with many types of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, upon overexpression of MEF2C, we observed an induction of 14-3-3g, Gadd45b and p21 transcripts, encoding inhibitors of the CYCLIN B1/CDK1 kinase. 24,[52][53][54][55][56] These genes have a role in the G2-M checkpoint both in normal cell cycle progression and in response to DNA damage. We also found that failure of MEF2C degradation correlates with an increase in the cytoplasmic inactive fraction of CYCLIN B1.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the mechanisms that lead to a decrease in cell-cell adhesion, we used a HCT116 cell line model in which 14-3-3c had been knocked down (sh14-3-3c) (described previously by Hosing et al, 2008). 14-3-3c mRNA and protein levels were lower in the sh14-3-3c cells in comparison with the control cells ( Fig.…”
Section: Loss Of 14-3-3c Leads To Sterility In Male Micementioning
confidence: 99%